Neutrophil-to-lymphocyte ratio is a reliable marker of treatment response in rheumatoid arthritis patients during tocilizumab therapy. Issue 3 (4th May 2017) - Ghang, Byeongzu; Kwon, Ohchan; Hong, Seokchan; Lee, Chang-Keun; Yoo, Bin; Kim, Yong-Gil
Abstract: Objective : To investigate the reliable markers reflecting treatment response better than the traditional inflammatory indices in patients with rheumatoid arthritis (RA) receiving tocilizumab therapy. Methods : A total of 58 RA patients treated with tocilizumab for more than six months from January 2013 to December 2014 were initially included. Flares were defined as events that required steroid dose escalation, intra-articular steroid injections, or switching tocilizumab to other biologic agents. The clinical and laboratory data were retrospectively collected from electronic medical records. Results : Of the 52 patients except for six patients who were excluded, 16 experienced flares, and 36 were stable during tocilizumab therapy. The C-reactive protein (CRP) level did not significantly differ between a stable state before flares and at flares. Compared with those at the preflare time point, erythrocyte sedimentation rate (ESR), and neutrophil to lymphocyte ratio (NLR) were significantly higher at flares; however, ESR levels ( n = 9) were within the normal limit or decreased ( n = 4) at flares. Interestingly, NLR increased at flares in all but one patient in the flare group. Conclusion : NLR is a more reliable marker than ESR or CRP for evaluating the disease activity in patients with RA during tocilizumab therapy.